Diet of South Polar Skua chicks in two areas of sympatry with Brown Skua - Graña Grilli, Maricel; Libertelli, Marcela; Montalti, Diego (Waterbirds)
The food provided to South Polar Skuas (Stercorarius maccormicki) chicks was determined at two Antarctic sites where South Polar Skuas breed sympatrically with Brown Skuas (S. antarcticus). At Harmony Point on Nelson Island, 16 samples of regurgitated stomach contents were analyzed, all contained remains of penguin chicks (mostly soft tissues), which constituted the bulk of the contents, while only two samples had fish or krill remains. These South Polar Skuas had access to penguin colonies, where they hunted chicks or fed on fresh carcasses. However, at Half Moon Island, only two out of nine samples contained minor amounts of penguin remains while fish were the major dietary resource. The high fish content in their diet may indicate a preference for marine rather than terrestrial resources or be the result of competition with Brown Skuas. The variability in food items evidenced by the differences in regurgitated stomach contents indicates that South Polar Skuas may have a trophic plasticity that allows them to change their feeding habits from one resource to another one according to availability. Such may make them less vulnerable to a reduction in the availability of a particular food item. Fil: Graña Grilli, Maricel. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Libertelli, Marcela. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Montalti, Diego. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Zoología de Vertebrados. Sección Ornitología; Argentina